Thermal analysis of Cu-14.82 wt% Al-0.4 wt% Be shape memory alloy - Canbay, Canan Aksu; Aydogdu, Ayse (Springer, 2013)
In the present study, the transformation temperatures and shape memory effect of the Cu-14.82 wt% Al-0.4 wt% Be shape memory alloy were studied. The structural properties of the alloys were characterized by X-ray diffraction. The crystal structure analysis of the alloy shows a thermoelastic transformation from an ordered parent-phase of DO3 type to the M18R martensite. The microstructure of the alloy was investigated by optical micrographs. The transformation temperatures, enthalpy and entropy values of the alloy were determined by differential scanning calorimetry. Thermogravimetric and differential thermal analysis measurements were performed to obtain the ordered-disordered phase transformations. The activation energy values determined from two different methods were found to be 306.53 kJ mol(-1) for Kissinger and 298.57 kJ mol(-1) Ozawa.
Keywords: Shape memory alloys; Transformation temperatures; Enthalpy; Entropy; CuAlBe